GAMBARAN PEMBERIAN IMUNISASI DASAR PADA MASA PANDEMI COVID-19 DI WILAYAH PUSKESMAS MARGADADI KABUPATEN INDRAMAYU - meran dewina (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2022)
In 2020, it’s been noted that the cause of postnatal death is due to pneumonia 73.9%, diarrhea 14.5%, meningitis etc. Since COVID-19 has disrupted health services, the national complete basic immunization coverage is 83.3%. This precentage has not met the 2020 strategic plan target (92.9%), including the West Java which only reached 83.7%. In addition, the number of infant deaths in Indramayu Regency is still high. Immunization is an important health service that aims to protecting children from death-caused diseases. This reasearch aims to determine the description of basic immunization during the COVID-19 in the Margadadi Health Center, Indramayu Regency. This research used descriptive quantitative and retrospective approach. The number of infant population is 787. It also used total sampling, secondary data and univariate data analysis. The result shows that the Achievement of HB immunization 0-7 days is 88.7%, BCG is 83.2%, Polio 1 is 82.7%, Polio 2 is 77.8%, Polio 3 is 75.6%, Polio 4 is 78.7%, DPT/ HB/HIB 1 is 79.4%, DPT/HB/HIB 2 is 74.7%, DPT/HB/HIB 3 is 76%, Measles is 82.5%, and the number infants who has been immunised is 16.6%. The description of basic immunization during the covid-19 has not yet fully achieved due to difficult access, the main focus of health services for covid-19 patients, the implementation of PKM, physical-social distancing, self-isolation, parental concerns about pandemic conditions, as well as delays in the distribution of vaccines for basic immunization. It is hoped that health workers will increase outreach activities on basic immunization, extend infant immunizations, and provide immunization services while implementing Covid-19 health protocols.